Influence of Communicative Openness on the Psychological Adjustment of Internationally Adopted Adolescents. (27th October 2018) - Aramburu Alegret, Inés; Pérez‐Testor, Carles; Mercadal Rotger, Josep; Salamero Baró, Manel; Davins Pujols, Montse; Mirabent Junyent, Vinyet; Aznar Martínez, Berta; Brodzinsky, David
Abstract : This study evaluated the predictive relationship between the communicative openness and psychological adjustment of adopted adolescents, controlling for preplacement risk factors. One hundred Spanish international adoptees aged 12–18 took part in the study. Data were gathered with a structured interview, the Youth Self Report and the Adoption Communication Scale. A history of maltreatment prior to the adoption was associated with more closed communication between parents and children. Prenatal drug exposure shows a relationship with the presence of externalizing behaviors and attention problems in adolescents. Finally, a lower degree of communicative openness regarding the child's origins was significantly associated with the presence of all the adolescent behavioral problems studied.